2002
DOI: 10.3171/spi.2002.97.4.0473
|View full text |Cite
|
Sign up to set email alerts
|

Use of a bioabsorbable anterior cervical plate in the treatment of cervical degenerative and traumatic disc disruption

Abstract: Object. Anterior cervical discectomy and fusion (ACDF) is a widely accepted treatment for anterior degenerative or traumatic instability of the cervical spine. To reduce or eliminate complications such as implant migration and failure, imaging degradation, and fusion stress shielding that are occasionally associated with spinal instrumentation, attention has been given to the use of bioresorbable anterior cervical plate (ACP) devices. This paper is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…Although a multitude of preceding studies have provided encouraging results for the use of bACPs, 2,8,16,18,20,23 other studies echo these concerns. Brkaric et al 4 reported early failure of the Mystique plate in 3 of 6 patients who underwent single-level ACDF.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although a multitude of preceding studies have provided encouraging results for the use of bACPs, 2,8,16,18,20,23 other studies echo these concerns. Brkaric et al 4 reported early failure of the Mystique plate in 3 of 6 patients who underwent single-level ACDF.…”
Section: Discussionmentioning
confidence: 90%
“…6 Several studies of biodegradable plating systems have reported conflicting results in bony fusion rates. [1][2][3][4]8,9,13,15,16,18,20,23,24 Vaccaro et al 23 described the first series of patients treated with a biodegradable anterior cervical mesh in 2002. The fusion rate was 77% (7/9 patients) at an average follow-up of 206 days for single-level ACDF without severe complications or revisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once adapted for use in spinal applications, RPSS's have been investigated for supplemental anterior fixation to cervical interbody fusion constructs. Although prospective randomized studies to date are limited, many retrospective analyses have concluded resorbable anterior cervical plating as a reasonable alternative to metal (Vaccaro et al 2002;Franco et al 2007;Tomasino et al 2009). RPSSs have also been considered for supplemental lumbar fixation (DiAngelo et al 2002), however in-vivo loading conditions of the lumbar spine may prove too intense for this application.…”
Section: Thermoplastic Spine Implantsmentioning
confidence: 99%
“…The patient was stabilized in a halo device for 24 h and surgical intervention was discussed with the family. After informed consent, the patient underwent anterior cervical corpectomy of C3 and the base of C2 with an autologous rib graft and C2-C4 anterior cervical plating with macropore [10]. Posteriorly the patient underwent occipital-C3 fusion with a titanium rod placed in a prepared midline trough and secured to the occiput with wires.…”
Section: Case Reportmentioning
confidence: 99%